Growth performance, digestive capacity and intestinal health of juvenile spotted seabass (Lateolabrax maculatus) fed dietary laminarin supplement - Qin, Huihui; Long, Zhongying; Ma, Jianrong; Kong, Lumin; Lin, Hao; Zhou, Sishun; Lin, Yi; Huang, Zhangfan; Liu, Longhui; Li, Zhongbao (Frontiers in Marine Science, 2023)
Laminarin has antioxidant, immunomodulatory and improved gut microbiota effects, providing a potential solution for the treatment of intestinal diseases in fish. The aim of this study was to investigate the effects of laminarin on the growth and intestinal health of juvenile spotted seabass. A total of 450 juveniles (initial body weight: 7.14±0.10 g) were randomly divided into 6 groups with 3 replicates per group and 30 fish per replicate. Six diets were prepared with laminarin supplementation at doses of 0% (Control), 0.4% (P0.4), 0.8% (P0.8), 1.2% (P1.2), 1.6% (P1.6) and 2% (P2), respectively. Each group was fed the corresponding diet for 8 weeks. The results indicated that dietary laminarin supplementation of 0.4%-1.6% improved the specific growth rate (SGR), weight gain rate (WGR) and feed coefficient (FCR) of juvenile spotted seabass, and the difference was significant in the P0.8 group (P<0.05). Compared with the control group, intestinal amylase and trypsin activities were significantly increased in P0.8 group (P<0.05), and lipase activities were significantly increased in P0.4, P0.8, P1.6, and P2 groups (P<0.05). In P0.8 group, the total antioxidant capacity, reduced glutathione, alkaline phosphatase and lysozyme were significantly increased (P<0.05), while the contents of diamine oxidase and D-lactic acid were significantly decreased (P<0.05). Furthermore, intestinal villus height, villus width and crypt depth were significantly increased in P0.8 and P2 groups (P<0.05), and muscular thickness was significantly increased in P1.2 group (P<0.05). Intestinal microbial analysis revealed that the alpha diversity of polysaccharide groups was significantly higher than that of the control group. Moreover, the abundance of intestinal beneficial bacteria Lactobacillus and Klebsiella in P0.4 and P0.8 groups was significantly increased (P<0.05), indicating that laminarin altered the composition of intestinal flora and the abundance of dominant bacteria, with a low dose being more conducive to the formation of beneficial bacteria. In conclusion, dietary laminarin supplementation can improve the growth performance and intestinal function of juvenile spotted seabass. The regression analysis of WGR and SGR showed that the optimal supplemental level of laminarin in diet was 0.96%. The results provided new insights into the application of laminarin in aquaculture.